Carrefour : retailing in an international marketplace - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
The French supermarket company, Carrefour, has grown to own a significant share of the global retail market. This case study examines how Carrefour has ensured its success in international markets by adapting its strategies, depending on local culture, economy or religious differences.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Carrefour: Retailing in an International Marketplace. In International marketing (pp. 34-35). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Carrefour (Market chain); Export marketing -- Case studies; Retail trade -- Case studies